The Development of Mobile Telephony in the World and in Croatia - Mikula, Miroslav; Šarić, Slavko; Peraković, Dragan (Promet - Traffic&Transportation, 2012)
The paper first describes the invention and introduction ofmobile telephony in the world and in Croatia. Then the basiccharacteristics are compared as well as the possibilities of certaingenerations of the mobile radio telephone systems with emphasison certain advantages. Finally, the prospects of furtherdevelopment of the mobile telephones are discussed, and theadequate conclusions made.